2022
DOI: 10.1111/hae.14557
|View full text |Cite
|
Sign up to set email alerts
|

Associated comorbidities, healthcare utilization & mortality in hospitalized patients with haemophilia in the United States: Contemporary nationally representative estimates

Abstract: Introduction Current in‐hospital burden and healthcare utilization patterns for persons with haemophilia (PWH) A and B, including both children (ages < 18 years) and adults (ages ≥ 18 years), in the United States (US) are lacking. Aim To evaluate healthcare utilization, the prevalence of comorbidities, and mortality in hospitalized paediatric and adult PWH using a contemporary nationally representative cohort. Methods Hospitalizations of PWH either as the primary reason for admission (principal diagnosis) or o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…One study by Day et al. [ 34 ] not included in Table 3 reported in-hospital mortality for admissions with hemophilia from 2017 and compared against all admissions. Although no numerical data are provided in that study, visual data show that mortality appears to be reduced in persons with hemophilia codiagnosed with nontraumatic ICH, acute myocardial infarction, and stroke when compared to all hospital admissions.…”
Section: Resultsmentioning
confidence: 99%
“…One study by Day et al. [ 34 ] not included in Table 3 reported in-hospital mortality for admissions with hemophilia from 2017 and compared against all admissions. Although no numerical data are provided in that study, visual data show that mortality appears to be reduced in persons with hemophilia codiagnosed with nontraumatic ICH, acute myocardial infarction, and stroke when compared to all hospital admissions.…”
Section: Resultsmentioning
confidence: 99%
“…The life expectancy of hemophiliacs has increased due to the wide availability of replacement therapies, and the comorbidities related to aging have become present. By analyzing more than 10,000 hospitalizations of hemophiliacs, it was found that HTN ranked first among the comorbidities, with it being identified in 33.4% of the admitted patients [ 72 ]. One study showed that among the cardiovascular diseases, HTN was the most common cause of an emergency department presentation [ 75 ].…”
Section: Discussionmentioning
confidence: 99%